Understanding the Relationship between Social Cognition and Word Difficulty - Aramaki, E.; Shikata, S.; Miyabe, M.; Usuda, Y.; Asada, K.; Ayaya, S.; Kumagaya, S. (Methods of Information in Medicine, 2015)
Background: Few quantitative studies have been conducted on the relationship between society and its languages. Individuals with autistic spectrum disorder (ASD) are known to experience social hardships, and a wide range of clinical information about their quality of life has been provided through numerous narrative analyses. However, the narratives of ASD patients have thus far been examined mainly through qualitative approaches.Objectives: In this study, we analyzed adults with ASD to quantitatively examine the relationship between language abilities and ASD severity scores.Methods: We generated phonetic transcriptions of speeches by 16 ASD adults at an ASD workshop, and divided the participants into 2 groups according to their Social Responsiveness ScaleTM, 2nd Edition (SRSTM-2) scores (where higher scores represent more severe ASD): Group A comprised high-scoring ASD adults (SRSTM-2 score: 76) and Group B comprised low- and intermediate-scoring ASD adults (SRSTM-2 score: < 76). Using natural language processing (NLP)-based analytical methods, the narratives were converted into numerical data according to four language ability indicators, and the relationships between the language ability scores and ASD severity scores were compared.Results and Discussion: Group A showed a marginally negative correlation with the level of Japanese word difficulty (p < .10), while the “social cognition” subscale of the SRSTM-2 score showed a significantly negative correlation (p < .05) with word difficulty. When comparing only male participants, Group A demonstrated a significantly lower correlation with word difficulty level than Group B (p < .10).Conclusion: Social communication was found to be strongly associated with the level of word difficulty in speech. The clinical applications of these findings may be available in the near future, and there is a need for further detailed study on language metrics designed for ASD adults.
Keywords: Autism; ASD; autistic spectrum disorder; language ability; natural language; social communication